Impact of a mindfulness‐based stress reduction program from the perspective of adolescents with serious mental health concerns. Issue 1 (10th June 2016) - Van Vliet, K. Jessica; Foskett, Allison J.; Williams, Jennifer L.; Singhal, Anthony; Dolcos, Florin; Vohra, Sunita
Abstract : Background: While studies on mindfulness‐based stress reduction (MBSR) for youth have recently emerged, there is a shortage of research on how adolescents from clinical populations experience MBSR. The purpose of this qualitative study was to explore the impact of MBSR from the subjective perspective of adolescents with serious mental health concerns. Method: Adolescents ( n = 28) from a residential treatment center participated in an adapted 8‐week MBSR program in which they learned a range of mindfulness skills and were encouraged to apply the skills to their everyday lives. At the end of the program and at a 3‐month follow‐up, the youth participated in semistructured interviews in which they were asked to describe the impact of the program from their perspectives. Basic interpretive qualitative analysis methods were used to code the data and to group the codes into higher level themes. Results: Six main themes were found, including improved mood, enhanced relationship to self, increased self‐control, improved problem‐solving, awareness of the present, and enhanced interpersonal relationships. Discussion: Results from this study suggest that the MBSR program was perceived as beneficial both in the short‐term and follow‐up in several aspects of emotional, cognitive, and interpersonal functioning.